ANALISIS KUALITAS MANAJER PROYEK TERHADAP PELAKSANAAN PROYEK KONSTRUKSI (STUDI KASUS : DI DENPASAR DAN BADUNG) - Eka Dharsika, I Gde; Budiartha, IN; Yansen, I W (JURNAL SPEKTRAN; Vol 5 No 1 (2017): Vol. 5, No. 1, Januari 2017, 2017)
Abstract : Problems in construction projects caused by the extension of working time and an increase in labor costs. A limited ability of project management contribute to the decline in the quality of project work. The quality of project manager has an important role to smooth a construction project. Dedication in this profession requires project managers to carry out the work going according to plan. Analyzing the quality of the project manager for the implementation of construction projectsis one wayto measure the quality of a project. It needs  a right measurements way to providean accurate assessment of qualified and reliable project managers. This study aimed to obtain and analyze the factors that affect the quality of the project manager and its to construction projects.This used a sample of 45 respondents from several construction projects in the area of Badung and Denpasar during the period 2007-2012. The method used in this study is the method of multiple linear regression analysis by testing for the F-test and t-test. The results found 8 dominant factor that has a value eigen values??> 1. Sequentially, the factors that have been named are experience 41.63%,  education 9.278%, knowledge 7.240%, ability 5.088%, character 4.047%, network 3.843%, relationship communication 3.550%, confidence 3.357%. Influence the quality of the project manager on the performance fee of 51.9%, against 43.1% for quality performance, on-time performance, with a value of 57.9%. The results of this study prove that the powerful influence between the quality of the construction project manager to the implementation of construction projects.
Keywords: Quality, manager, project, factor analysis